Muscle activation characteristics of tumbling take-offs - McNeal, J. R.; Sands, W. A.; Shultz, B. B. (Sports Biomechanics, 2007)
In the floor exercise, a gymnast may receive a general composition score deduction associated with a lack of diverse tumbling sequences. Diversity in tumbling is defined as the ability to tumble both forward and backward, as well as twist and flip. A coach's ability to direct technical and physical training for these skill varieties is enhanced when thorough descriptions of the skills are available. The aim of this study was to describe and compare muscle activation of the lower extremity in various tumbling sequences characterized by differing body orientations. The stretch-shortening cycle actions during the take-off portion of four different tumbling sequences were analysed and the results compared across muscles and type of take-off (forward vs. backward, twisting vs. non-twisting). Thirteen female gymnasts performed three trials each of round-off flic-flac to backward layout and to backward layout with longitudinal axis twist, and front flic-flac to forward layout and to forward layout with longitudinal axis twist. Activation onset was assessed as an increase of the EMG of 200% above noise before initial floor contact. The EMG was normalized to peak values for each muscle bilaterally during each take-off. Results showed that muscle activation characteristics in the pre-activation and impact phase (contact to maximal floor depression) differed between tumbling series. Backward take-offs were characterized by longer contact times, greater relative activity of the gastrocnemius compared with the vastus lateralis during pre-activation, and greater biceps femoris activation during impact compared with forward take-offs. Twisting backward was associated with reduced muscle activity of the twisting limb, while twisting forward was associated with increased muscle activation on the twisting limb. These differential effects related to the specific nature of the take-off indicate that training to enhance the stretch-shortening cycle action in gymnasts must be specific to the orientation requirements of each specific skill.